Optimization of g-C3N4 nanoparticles on structural, morphological, and optical properties as organic pollutants adsorbent in glycerin - Lutfi Chabib; Nursal; Mazidatulakmam Miskam; Noor Haida Mohd Kaus; Muhammad Hakimin Shafie; Muhammadin Hamid; Indah Revita Saragi; Isnaeni Isnaeni; Dinda Amilia; Ivi Briliansi Dalimunthe; Hadi Wijoyo (Case Studies in Chemical and Environmental Engineering)
Addressing the issue of organic pollutants in the environment has become a hot topic among researchers. Therefore, this study aims to degrade an organic pollutant, precisely glycerin solution, using graphite carbon nitride (g-C3N4) nanoparticles through adsorption. Subsequently, tests were conducted based on morphological, structural, and optical properties. The results obtained in this study are as follows: XRD analysis showed a significant peak at 27.74°, confirming the material's layered structure and good crystallinity. HR-TEM analysis revealed an optimal average particle size of 8.87 nm. FTIR analysis identified key functional groups contributing to degradation activity. UV–Vis analysis indicated a band gap of 2.31 eV, enabling effective visible light absorption.Additionally, PL spectra demonstrated luminescence properties with peaks at 464 nm and 495 nm, indicating potential applications in photonics and sensors. The adsorption capacity obtained from glycerin degradation was 6.5 mg/g, which is a good result. These findings highlight the structural integrity of g-C3N4, optimal particle size, and favorable optical properties as significant factors that make g-C3N4 highly appealing for degradation materials.